Apology Strategies Used by Chad Griffin Addressed to The Lesbian, Gay, Bisexual and Transgender Community - Danar Bawana Rama; Sri Endah Tabiati; Indah Winarni (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2018)
Apology Strategies is a study of speech act investigating how people use language as a mean to repair certain condition between speaker and hearer. There are many ways for people to deliver an apology. We often experience and hear a speaker apologizes without saying the word “sorry” or “apologize”. This article discusses Chad Griffin’s apology as the HRC (Human Right Campaign) leader to the LGBT (Lesbian, Gay, Bisexual and Transgender) Community. The result of this research shows that there are twenty-one apology utterances delivered by Chad Griffin. From those utterances there are ten utterances are identified as belong to the category of Indirect Apology strategy, thirteen utterances belong to the category of Remedial Support, three utterances belong to Direct Apology Strategy and only one utterance is as Evasive Strategy.